Investigation of Electrokinetic Properties of Natural Vine Stem Dispersions as Biosorbent - Mavioglu Ayan, Ebru; Evrim Yalcinkaya, Esra; Toptas, Asli (Asian Journal of Chemistry, 2014)
Vine stem is used as a low cost adsorbent for the removal of toxic dyes from the aqueous solutions. In this study, the effects of electrolyte concentration, pH and type of ionic species on the zeta potential of the natural vine stem dispersions were investigated by microelectrophoresis method. z-Potential experiments have been performed to determine the point of zero charge (pzc) and potential determining ions (pdi). The surface charge of vine stem exhibited an increasing negativity as the pH of the solution increased. Vine stem dispersions do not have point of zero charge. A gradual decrease in the z-potential occurs with the monovalent electrolytes when concentration increased. Divalent and heavy metal electrolytes have less negative potentials due to the higher valence of ions. The z-potential values have had a positive sign at trivalent electrolytes.